The effect of preexisting fracture angles on crack propagation in sandstone - Mughieda, Omer S.; Namdar, Abdoullah; Alzaylaie, Marwan; Abdul Syukor, Abd Razak (John Wiley and Sons Ltd, 2025)
The fracture propagation on the rock causes failure and impacts the sustainability time of the structure. As part of the present work, sandstone with the variation of preexisting crack angle was simulated using the extended finite element method (XFEM). The crack propagation on sandstone has a preexisting fracture angle of 30°, 45°, and 60°, with an equivalent crack length. The impact of preexisting fracture angle on the possibility of crack propagation, failure mechanism, and displacement at a critical point of all models was studied. The numerical simulation revealed the crack angle of the model control vibration and its impact on the model’s seismic stability. The XFEM results are validated with reference to those available in the literature. Artificial neural networks (ANNs) are used for prediction by considering the training, testing, and validation process and analyzing prediction errors. The present simulation’s conclusion significantly supports the model’s displacement prediction with no crack propagation occurrence. In addition, by considering the preexisting fracture angle of a model, the load sustainability can be estimated.